The Influence of Teacher Creativity on Understanding Tolerance Material in Class XI Islamic Religious Education Subjects at SMA Negeri 2 Cepu - Ahmad Muthi’ Uddin; Ulva Badi’ Rohmawati; Nur Alfiyah (al-Afkar, Journal For Islamic Studies, 2024)
This research was motivated by the lack of understanding of tolerance in class XI SMA Negeri 2 Cepu. The purpose of this study was to determine whether there was an influence between teacher creativity on students' understanding of tolerance material in Islamic Religious Education subjects in class XI SMA Negeri 2 Cepu. This research uses a quantitative approach and the type of associative research. The data analysis used by the researcher is Person Product Moment with the aim of knowing the relationship between the independent variables and the dependent variable. In collecting data  the  researchers  used  a  questionnaire  to  determine  and  measure  the  creativity  of teachers  and  a  test  to  determine  and  measure  students'  understanding  of  the  tolerance material for class XI SMA Negeri 2 Cepu. Based on the research conducted, the results showed that there was an influence of teacher  creativity  on  students'  understanding  of  tolerance  material  in  Islamic  Religious Education subjects in class XI SMA Negeri 2 Cepu. The results obtained from the correlation test are rcount greater than rtable   or 0.768 > 0.3338 which is in the interval 0.70 – 0.90 at the level of the relationship, namely strong or high. With a value of Sig (2-tailed) that is 0.000 <0.05, which means that there is an influence between two variables.